y^3 - t^3 or x^3 - y^3 is the same if you are more comfortable
(x-y) * (x^2 - y^2) -----> (x - y) * (x - y) * (x + y)
1) x - y = 3 -----> 3 * 3 * (x + y) ----> we do no have the value od (x + Y)
2) we have 21 BUT not (x - y)
1) + 2) we have 3 * 21 ----> Sufficient
You are right that it does not make any difference between y,t & x,y.
But you made a mistake in the formula \(x^3-y^3\) is not equal to \((x-y)\) * \((x^2 - y^2)\)
Instead \((x-y)^3\) is equal to \(x^3-y^3\) + \(3xy(x-y)\)
I Hope it helps.
If you like my Question/Explanation or the contribution, Kindly appreciate by pressing KUDOS.
Kudos always maximizes GMATCLUB worth -Game Theory
If you have any question regarding my post, kindly pm me or else I won't be able to reply